Between Maternity and Autonomy: Radical Mothering in Mona Simpson's Anywhere but Here. Issue 2 (15th March 2022) - Krishna, Swathi; Chatterjee, Srirupa
ABSTRACT: This essay argues that Mona Simpson's Anywhere but Here (1986) sustains a path breaking debate on maternity vis-à-vis female autonomy. It examines how in a narrative spatiotemporally located in America's Midwest during the conservative eighties, the nurturing and selfless maternal figure of white middle-class Christian homes is replaced by a self-seeking maverick, Adele, who uncompromisingly embodies the hopes and aspirations of the contemporary everywoman. By underscoring how Adele rejects domesticity, rewrites male quest narratives, and survives her ambitious journeys with the help of the bond she shares with her daughter, Ann, this essay claims that Simpson's fictional mother radically subverts all conventional caregiving practices. Further, by highlighting the seemingly conflicting discourses of maternity and autonomy which characterize Adele, this essay with the help of matricentric feminist theorists and post-Freudian psychoanalysts establishes that Anywhere but Here redefines not only the mother-child bond but also the maternal figure to engender a compelling narrative on women's empowerment that resonates deeply with current conversations surrounding motherhood.